Development of a patient-centered peer-mentoring program for kidney transplant patients: a qualitative study - Kumnig, Martin; Jowsey-Gregoire, Sheila; Gruber, Anna; Kofler, Matthias M.; Gordon, Elisa J. (Frontiers in Psychology, 2025)
BackgroundEnd-stage kidney disease (ESKD) causes physical and mental challenges to affected patients that complicates their ability to manage pre-transplant medical care. Patients benefit from both education about their treatment options, and social support. Peers can address these needs if provided with suitable instruction and direction. This study identified patient-centered components of a peer-mentoring program for kidney transplant recipients based on the input from recipients and providers.MethodsWe conducted semi-structured videoconferences with kidney transplant recipients (KTRs) to assess experiences of the pre-transplant evaluation process, post-transplant recovery, living with a kidney transplant, and preferences of a peer-mentoring program. Transcripts were analyzed using thematic analysis.ResultsA total of 44 KTRs participated. Four themes emerged about integral components of a patient-centered peer-mentoring program: psychosocial challenges and adjustment after transplantation; navigating complex information and the effects of trusted peer experiences; the qualifications, role, and tasks of peer mentors; and barriers and facilitators to engaging in peer support. Participants recommended that peer mentors possess certain characteristics (e.g., communicational/psychological skills) and provide support (e.g., low-threshold sharing of information and experiences). Optimal peer-mentoring programs should adapt to patients' needs, address QOL concerns and transplant outcomes, and be easily available. Peer-mentor training should cover transplant-related medical information, the role of a peer mentor, communication training, and information about patient advocacy tasks.ConclusionsThis study provides insights into developing and implementing a kidney peer-mentoring program. Future research should adapt currently existing peer-mentoring programs to accommodate these patient-centered qualities and evaluate accordingly.